2021
DOI: 10.1016/j.joule.2021.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic analysis of long-duration energy storage and flexible power generation technologies to support high-variable renewable energy grids

Abstract: Solar and wind energy are being rapidly integrated into electricity grids around the world. As renewables penetration increases beyond 80%, electricity grids will require long-duration energy storage or flexible, low-carbon electricity generation to meet demand and help keep electricity prices low. Here, we evaluate the costs of applicable technologies based on current technology status and future projections. We show which technologies have the lowest costs and identify opportunities for each to help decarbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(73 citation statements)
references
References 48 publications
1
72
0
Order By: Relevance
“…If ammonia is only used as an energy storage medium, a positive revenue of US$15.3 million will be obtained, which is still US$258 million lower than electricity export. Yet this difference might be compensated by the benefits of large-scale ammonia energy storage on the grid ( Dowling et al., 2020 ; Hunter et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…If ammonia is only used as an energy storage medium, a positive revenue of US$15.3 million will be obtained, which is still US$258 million lower than electricity export. Yet this difference might be compensated by the benefits of large-scale ammonia energy storage on the grid ( Dowling et al., 2020 ; Hunter et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The authors built a multi-state probabilistic model of main components in the power system and proposed flexibility metrics for the analysis of the measures proposed. More studies on RE-based flexibility strategies and challenges for power systems are reported in [117][118][119][120].…”
Section: Flexibility Improvement With Renewable Energy Sourcesmentioning
confidence: 99%
“…For context, the peak electric power demand in Texas was 72 GW in 2018, and U.S.-wide annual hydrogen consumption in 2015 was ~10 MT/year. 35 While the electricity demand could be large, the potential for flexible operation, particularly for low-temperature electrolyzers, 43 coupled with the relatively low capital cost of hydrogen storage vs. Li-ion energy storage, 44 creates an opportunity to schedule electrolytic hydrogen production as a flexible load to balance fluctuations of renewables in future power grids. Importantly, flexible hydrogen production can still serve baseload hydrogen demand from industrial applications.…”
Section: Hydrogen As a Vector For Electrodecarbonizationmentioning
confidence: 99%